Costs of Outpatient Anticoagulant Treatment in Patients with Cerebral and Peripheral Arterial Occlusive Disease - the Dutch BOA Study Group; for the Stroke Prevention in Reversible Ischemia Trial (SPIRIT) Study Group; Gorter, J. W.; Oostenbrink, J. B.; Tangelder, M. J. D. (Thrombosis and Haemostasis, 2001)
Background and objective: Knowledge of the costs of oral anticoagulant (AC) treatment may be relevant for resource allocation. Also, the incremental costs may be compared with other treatments for health care policy decisions. In this report, we have assessed actual costs of anticoagulant therapy in anticoagulation clinics (AC-clinic) in three different settings in the Netherlands. Methods: Costs of anticoagulant drug supply and costs as a result of INR-adjustment procedures were estimated. We compared the total costs of treatment in patients treated after minor cerebral ischaemia in the Stroke Prevention in Reversible Ischemia Trial (SPIRIT) and in patients treated because of peripheral arterial occlusive disease in the Dutch Bypass Oral anticoagulants or Aspirin Trial (BOA). Results: Costs of monitoring ranged between Euro 6.44 and Euro 9.87 per visit for monitoring at the AC-clinic and at home, respectively. The annual costs of administering anticoagulant drugs ranged between Euro 83 (phenprocoumon) and 107 (acenocoumarol). Variation in the overall actual annual costs of AC treatment was caused by the number of monitoring visits, the distribution of home and clinic visits and, to a lesser extent, the medication used. Annual costs of AC therapy for patients in SPIRIT was Euro 239 and for patients in BOA Euro 312. Overall costs of anticoagulant therapy were about 3 to 4-fold higher than standard treatment with aspirin. Conclusions: Although the actual costs of anticoagulant therapy may be substantially higher than that of other antithrombotic therapies, its cost-effectiveness depends highly on efficacy.Writing Committee: A. Algra MD, E. Buskens MD, J. W. Gorter MD, J. B. Oostenbrink MSc, M. J. D. Tangelder MD.Extended writing committee: All above authors plus: B. C. Eikelboom MD, B. A. van Hout PhD, J. van Gijn MD, L. J. Kappelle MD, P. J. Koudstaal MD, J. A. Lawson MD, J. de Vries-Goldschmeding, MD (on behalf of the Federatie van Nederlandse Trombosediensten), and the SPIRIT and Dutch BOA Study Groups.
Keywords: Oral anticoagulants; costs; the Netherlands; secondary prevention